Differentiation, multiplication and control of bloodstream form Trypanosoma (Duttonella) vivax in mice - Mahan, S.M.; Black, Samuel J. (Wiley, 1989)
.The growth and differentiation of Trypanosoma vivax was studied in intact and irradiated C3H/He and C57B1/6 mice. In irradiated (800 R) or intact C3H/He and irradiated (800 R) C57B1/6 mice, T. vivax parasitaemia increased rapidly then entered a plateau phase and thereafter declined in an antibody‐independent remission phase. Throughout the infection, variations were observed in parasite morphology, density, DNA content, number of organisms with 2 nuclei and 2 kinetoplasts and infectivity of parasites for mice. Parasites in exponential phase had the highest number of members in the S, G2 and M phases of the cell cycle as determined by staining with the interchalating dye Chromomycin A, and analysis on a flow cytometer. During this phase there were numerous parasites with 2 nuclei and 2 kinetoplasts and infectivity was high for mice. As the parasitaemia approached and entered the plateau phase, the proportion of organisms in the S, G2 and M phases of the cell cycle as well as the number of those with 2 kinetoplasts decreased slightly; the number of organisms with 2 nuclei decreased rapidly; and parasites had a considerably reduced capacity to infect mice. Organisms from the remission phase contained only 1 nucleus and 1 kinetoplast and were not infective for mice. The study suggests that T. vivax organisms transit from dividing to committed non‐dividing forms and that some non‐dividing, non‐infective T. vivax organisms remain trapped in the S, G2 and M stages of the cell cycle and die without completing binary fission. In contrast to the above, parasite wave remission occurred in T.vivax‐infected intact C57B1/6 mice during exponential growth when there were large numbers of dividing form organisms present in the bloodstream as determined by both DNA content and the proportion of parasites with 2 kinetoplasts and 2 nuclei. Clearance of T. vivax from the bloodstream of infected intact C57B1/6 mice coincided with the production of a parasite‐specific antibody response. The studies are discussed with reference to the mode of induction of host protective antibody responses to exponentially growing T. vivax.